2018
DOI: 10.1111/acel.12837
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase‐1 induction attenuates senescence in chronic obstructive pulmonary disease lung fibroblasts by protecting against mitochondria dysfunction

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with lung fibroblast senescence, a process characterized by an irreversible proliferation arrest associated with secretion of inflammatory mediators. ROS production, known to induce senescence, is increased in COPD fibroblasts and mitochondria dysfunction participates in this process. Among the battery of cellular responses against oxidative stress damage, heme oxygenase (HO)‐1 plays a critical role in defending the lung against oxidative stress and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 34 publications
(43 reference statements)
1
28
0
Order By: Relevance
“…In at least 1 study, exogenous mtDNA given intravascularly to rodents did not increase circulating mtDNA but increased u-mtDNA (26). U-mtDNA may also originate from renal cells, including glomerular or tubular epithelial cells (56), endothelial cells (44), and immune cells (6,12), as well as lung-derived cell sources (5)(6)(7)(8)(9)(10)(11)16) or muscle (65); further mechanistic studies are needed to identify the source of extracellular mtDNA in COPD. Whether u-mtDNA in COPD is a marker of disease or is pathogenic in itself remains to be determined.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…In at least 1 study, exogenous mtDNA given intravascularly to rodents did not increase circulating mtDNA but increased u-mtDNA (26). U-mtDNA may also originate from renal cells, including glomerular or tubular epithelial cells (56), endothelial cells (44), and immune cells (6,12), as well as lung-derived cell sources (5)(6)(7)(8)(9)(10)(11)16) or muscle (65); further mechanistic studies are needed to identify the source of extracellular mtDNA in COPD. Whether u-mtDNA in COPD is a marker of disease or is pathogenic in itself remains to be determined.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…One underlying biological mechanism that may provide insight into COPD pathogenesis and progression is mitochondrial dysfunction, which is consistently observed in cells derived from COPD subjects (5)(6)(7)(8)(9)(10)(11)(12)(13), as well as in experimental COPD models (11,14). Such mitochondrial dysfunction is associated with the leakage of mitochondrial DNA (mtDNA) (15)(16)(17)(18)(19), a mitochondrial derived danger-associated molecular pattern (mtDAMP) (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Mediators of Inflammation severity of COPD [33,34]. We evaluated the protein levels of Nrf2 and its major downstream factor HO-1 in the lungs of rats by Western blot.…”
mentioning
confidence: 99%
“…HO‐1 signal activation exerts a protective effect by preventing oxidative stress damage by accelerating catabolism of pro‐oxidant haem and oxygen‐free radicals (Lin et al, ). HO‐1 is expressed at low physiological levels, which can be increased via external stimulation, such as hypoxia, oxidative stress, inflammatory reactions, haem, endotoxins and heavy metals (Even et al, ). Our group found that increased HO‐1 expression begins 6 hr after ICH and that this change is consistent with the peak time of brain oedema (Yin, Chen, Zhou, Wu, & Bao, ).…”
Section: Introductionmentioning
confidence: 99%